Global trends in tertiary lymphoid structures: a bibliometric analysis from 2014 to 2023 - Bao, Yiwen; Mo, Zeming; Wang, Shuang; Long, Jinhua; Zhang, Honghong; Xu, Yujun; Jiang, Honglian; Qian, Tianbao; Zeng, Zhu (Frontiers in Immunology, 2024)
Aim and backgroundTertiary lymphoid structures (TLS) are increasingly recognized for their role in immunity. Despite growing interest, a systematic bibliometric analysis of TLS-related research has been lacking. To provide a comprehensive overview of current research trends and hotspots, we conducted a bibliometric analysis using data from the Web of Science Core Collection.MethodsWe retrieved TLS-related publications from the Science Citation Index Expanded within the Web of Science Core Collection from January 2014 to December 2023. Co-occurrence analysis with “VOSviewer” identified current status and research hotspots, while “CiteSpace” was used for co-citation analysis to assess knowledge evolution and bursts. Thematic evolution was explored using bibliometrics to identify emerging keyword trends. Additionally, we examined country/region, institutional, and author contributions and collaborations. Tables were created using Microsoft Word.ResultsA total of 785 publications were analyzed, showing a continuous growth trend from 2017 to 2023, indicating escalating interest in TLS among researchers. Leading countries in TLS research were China (231 publications), the United States (212 publications), and France (89 publications). The most productive institution and author were the “Institut national de la santé et de la recherche médicale” (70 publications) and Catherine Sautes-Fridman (21 publications), respectively. Key topics included TLS, B cells, and immunotherapy. Recent research has focused on mechanisms linking TLS with cancers, such as immunotherapy, tumor microenvironment, tumor-infiltrating lymphocytes, prognosis, and immune checkpoint inhibitors, highlighting an expanding area of study. Additionally, TLS’ potential as a biomarker for predicting immunotherapy efficacy across different cancer types remains a burgeoning research direction.ConclusionsThis study provides a comprehensive analysis of global TLS-related publications, revealing key literature metrics and identifying influential articles and emerging research concerns. These findings contribute valuable insights into the role of TLS in immunotherapy and suggest future directions for this dynamic field.